Faktor-Faktor Lingkungan dan Perilaku Yang Berhubungan dengan Kejadian Filariasis di Kabupaten Bangka Barat - Nasrin, Nasrin; Setiani, Onny; Budiyono, Budiyono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2009)
ABSTRACT Background : West Bangka district is one of the endemic areas of filariasis in Indonesia. In 2007, It was found about 36 chronic cases of filariasis. The high incidence of filariasis cases in West Bangka Regency was caused by many factors in the environment, such as swamp and ponds or hole in tin mining area which was flooded when raining or in rainy seasons. The aim of this research was to find out factors related to the filariasis incidence in West Bangk Regency. Method : It was an observational research using case control design. The subjects of this research was devided in two groups: cases and controls with 37 subjects of each group. The variables assessed in this research including physical factors (swamp / pool), Biological (water plants, fish/animal predators) for the environmental factors and education, job and income as socioecomic factor Behavioural factors were consisted of hanging out habit at night, wearing clothes to protect mosquitoes bite that might influenced the filariasis incidence in West Bangk Regency. The data were analyzed using multiple logistic regression at 5% level of significance. Result : The result of this research showed that there were seven variabels asrisk factors of filariasis incidence in West Bangka Regency,including: respondent’s job with OR = 3,695, respondent’s income level with OR = 4,2, the existence of swamp OR = 3,151, habit of using mosquito repellent with OR = 5,063, respondent’s knowledge about filariasis OR = 4,259, respondent’s knowledge about filariasis infection with OR =3,571 and respondent’s knowledge about filariasis prevention OR= 3,73. Conclusion : Environmental and behavioural factor were related to filariasis incidence in West Bangka District. It was recommended to improve those factors by implementing health promotion intensively. Keyword : Filariasis, enviromental and behavioral factors, West Barat District.